The effect of exhalation before the inhalation of dry powder aerosol drugs on the breathing parameters, emitted doses and aerosol size distributions - Árpád Farkas; Gábor Tomisa; Szilvia Kugler; Attila Nagy; Attila Vaskó; Erika Kis; Georgina Szénási; Gabriella Gálffy; Alpár Horváth (Elsevier, 2023)
Airway deposition of aerosol drugs is highly dependent on the breathing manoeuvre of the patients. Though incorrect exhalation before the inhalation of the drug is one of the most common mistakes, its effect on the rest of the manoeuvre and on the airway deposition distribution of aerosol drugs is not explored in the open literature. The aim of the present work was to conduct inhalation experiments using six dry powder inhalers in order to quantify the effect of the degree of lung emptying on the inhalation time, inhaled volume and peak inhalation flow. Another goal of the research was to determine the effect of the exhalation on the aerodynamic properties of the drugs emitted by the same inhalers. According to the measurements, deep exhalation before drug inhalation increased the volume of the inhaled air and the average and maximum values of the inhalation flow rate, but the extent of the increase was patient and inhaler specific. For different inhalers, the mean value of the relative increase in peak inhalation flow due to forceful exhalation was between 15.3 and 38.4% (min: Easyhaler®, max: Breezhaler®), compared to the case of normal (tidal) exhalation before the drug inhalation. The relative increase in the inhaled volume was between 36.4 and 57.1% (min: NEXThaler®, max: Turbuhaler®). By the same token, forceful exhalation resulted in higher emitted doses and smaller emitted particles, depending on the individual breathing ability of the patient, the inhalation device and the drug metered in it. The relative increase in the emitted dose varied between 0.2 and 8.0% (min: Foster® NEXThaler®, max: Bufomix® Easyhaler®), while the relative enhancement of fine particle dose ranged between 1.9 and 30.8% (min: Foster® NEXThaler®, max: Symbicort® Turbuhaler®), depending on the inhaler. All these effects and parameter values point toward higher airway doses due to forceful exhalation before the inhalation of the drug. At the same time, the present findings highlight the necessity of proper patient education on the importance of lung emptying, but also the importance of patient-specific inhaler-drug pair choice in the future.